INTERACTION OF THE Fe/γ-Al2O3 CATALYTIC SYSTEM WITH PROBE MOLECULES III. STUDY OF THE INTERACTION OF AMMONIA WITH γ-Al2O3 OXIDE AND THE Fe/γ-Al2O3 SYSTEM - Brodskiy A.R.; Grigoriyeva V.P.; Komashko L.V.; Nurmakanov Y.Y.; Chanysheva I.S.; Shapovalov A.A.; Shlygina I.A.; Yaskevich V.I. (Academic Scientific Journal of Chemistry, 2020)
The work is devoted to the study of the interaction of heterogeneous catalytic systems with adsorbed molecules. It presents the results of the interaction of the initial γ-Al2O3 oxide and the Fe/γ-Al2O3 system with ammonia obtained using IR spectroscopy and the method of temperature programmed desorption. Lewis and Bronsted acid centers were detected on the surface of both γ-Al2O3 oxide and the Fe/γ-Al2O3 system during their interaction with ammonia in the temperature range 293-773K using IR spectroscopy. The relative intensity of the absorption bands corresponding to these centers depends on the temperature of interaction with ammonia. It was found by ammonia TPD that adsorbed NH3 is desorbed in the form of five peaks from the γ-Al2O3 surface on a temperature scale, and in the form of seven peaks from the surface of the Fe/γ-Al2O3 system. It was shown that the total amount of desorbed ammonia decreases markedly with increasing adsorption temperature. Moreover, for individual temperature peaks, the amount of adsorbed ammonia can either decrease, pass through an extremum, or remain approximately constant. The appearance of additional desorption peaks for the Fe/γ-Al2O3 system is associated with iron deposited on alumina. Proceeding from the temperature range of existence of desorption peaks for γ-Al2O3 oxide and the Fe/γ-Al2O3 system it was established that they contain weak acid centers (desorption temperature up to 523K), acidic centers of medium strength (desorption temperature from 523 to 613K) and strong acid sites (desorption temperature above 613K). The volume of desorbed ammonia in the indicated temperature ranges can serve as a quantitative measure of various types of acid sites.